2013
DOI: 10.1038/modpathol.2012.242
|View full text |Cite
|
Sign up to set email alerts
|

Expression profiling of 519 kinase genes in matched malignant peripheral nerve sheath tumor/plexiform neurofibroma samples is discriminatory and identifies mitotic regulators BUB1B, PBK and NEK2 as overexpressed with transformation

Abstract: About 50% of all malignant peripheral nerve sheath tumors (MPNSTs) arise as neurofibromatosis type 1 associated lesions. In those patients malignant peripheral nerve sheath tumors are thought to arise through malignant transformation of a preexisting plexiform neurofibroma. The molecular changes associated with this transformation are still poorly understood. We sought to test the hypothesis that dysregulation of expression of kinases contributes to this malignant transformation. We analyzed expression of all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 52 publications
3
19
0
Order By: Relevance
“…Similarly, in the first systematic examination of Nek2 protein expression in CRC to date, we confirmed that Nek2 was overexpressed in 86.4% of resected CRC, with expression correlating with advancing AJCC stage and poor prognosis, and being maintained at secondary sites. These findings are in line with data for other solid and haematological malignancies and highlight Nek2 as a frequently overexpressed protein in human cancer .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Similarly, in the first systematic examination of Nek2 protein expression in CRC to date, we confirmed that Nek2 was overexpressed in 86.4% of resected CRC, with expression correlating with advancing AJCC stage and poor prognosis, and being maintained at secondary sites. These findings are in line with data for other solid and haematological malignancies and highlight Nek2 as a frequently overexpressed protein in human cancer .…”
Section: Discussionsupporting
confidence: 90%
“…The current study demonstrated correlations between Nek2 protein expression and tumour stage and prognosis in CRC, similar to findings reported for several other malignancies . The association of Nek2 with aggressive tumour biology is, therefore, a recurrent finding.…”
Section: Discussionsupporting
confidence: 89%
“…(17;18) For example, expression profiling in matched malignant peripheral nerve sheath tumors and neurofibroma samples did identify more than 500 kinase genes that are differentially expressed between both entities, with mitotic regulators BUB1B , PBK and NEK2 being overexpressed in malignant peripheral nerve sheath tumors. (19) However, the patterns of these changes turned out to be complex and heterogeneous, without a single unifying alteration that could be used as a diagnostic marker. In contrast, staining for H3K27me3 seems to be a more promising and easy to use diagnostic tool, in which loss of H3K27me3 favours progression to malignant peripheral nerve sheath tumors above plexiform or atypical neurofibroma.…”
Section: Discussionmentioning
confidence: 99%
“…The bioinformatic analysis revealed that Nek2 may directly or indirectly interact with a number of genes, proteins, microRNAs associated with drug resistance in ovarian and other types of cancer (28). Aberrant Nek2 expression has also been found in other cancers, such as non-small cell lung cancer and malignant peripheral nerve sheath tumor (29,30). …”
Section: Introductionmentioning
confidence: 99%